Prevalence and risk factors for diarrhea among children aged less than two years in Central Kalimantan Province, Indonesia - Suyitno, Suyitno; Chompikul, Jiraporn; Tiraphat, Sariyamon; Anye, Khin Sandar (Journal of Public Health and Development, 2019)
Diarrheal disease among children remains a major cause of morbidity and mortality worldwide. The youngest children are most vulnerable with the highest incidence of severe diarrhea in the first two years of life. A cross-sectional study was conducted to determine prevalence and risk factors for diarrhea in children aged less than two years in Central Kalimantan Province, Indonesia. The multi-stage cluster sampling was used to draw a sample of 469 respondents. The data collection was conducted from March to April 2018 using a structured questionnaire. Data were analyzed using Chi-square tests and multiple logistic regression to examine factors associated with diarrhea. The results of this study showed that all of the respondents were females. Prevalence of diarrhea during the last two weeks in children aged less than two years was 16%. The results of multiple logistic regression showed that caregivers who had low family income (Adj. OR= 6.53, 95% C.I=2.99-14.25), poor practice of food preparation (Adj. OR=9.61, 95% C.I=4.15-22.30), poor to moderate knowledge about diarrhea and prevention (Adj. OR=5.17, 95% C.I=2.35-11.38) and poor healthcare accessibility (Adj. OR=5.88, 95% C.I=2.74-12.63) were statistically significant risk factors for diarrhea in children aged less than two years. These findings suggested that public health providers should design public health programs for public health centers to provide mothers, other family members and caregivers with health information regarding diarrhea prevention. Comprehensive information should be delivered, including food preparation, feeding behavior and good formula milk feeding practice to their children.